A multi-sampling approach to evaluate an infrared surface treatment for reducing Listeria monocytogenes contamination on whole Gorgonzola cheese rinds. (September 2015) - Bernini, Valentina; Dalzini, Elena; Lazzi, Camilla; Bottari, Benedetta; Bisotti, Stefano; Fontana, Mauro; Neviani, Erasmo
Abstract: The microbial ecology of Gorgonzola cheese rind is the focus of many studies because the surface can be contaminated by pathogenic microorganisms. Among food-borne pathogens, particular attention is focused on the behaviour of Listeria monocytogenes that is able to grow at refrigeration temperatures and it could also grow during ripening. The Consortium for the Protection of Gorgonzola Cheese declares the rind not edible but the pathogen may also be transferred during cutting and portioning. Therefore, the decontamination of rinds is important to increasing cheese safety. To achieve this goal, many different strategies have been proposed. In this study, the application of an infrared surface treatment to decontaminate cheese rinds is proposed. The presence of L. monocytogenes, which was artificially inoculated in cheese rinds together with cheese rind microflora, and the cheese rind microflora were monitored before and after the treatment of 32 samples of Gorgonzola cheese rinds. The infrared surface treatment provided good reduction of the rind microflora, and L. monocytogenes was particularly affected by this. The treatment, applied to cheeses at the end of ripening, does not interfere with the ripening process and offers the advantages of short time exposures and easy installation of the equipment in cheese plants. Moreover, this study demonstrated that the sampling method affects the detection of cheese rind microflora. In fact, a non-destructive sampling method, based on a sponge and often used for surface sampling but never before applied to ready to eat food sampling, was compared with a traditional but destructive method, based on rind scraping. Regarding L. monocytogenes, the sponge method allowed to estimate even only 5.71 ± 0.79 log cfu g −1 of cells reduction after the treatment while the higher reduction when considering the rind scraping method was 4.06 ± 3.38 log cfu g −1 . The sponge method, combined with the classic scraping one, besides offering the great advantage of not being destructive, allowed to differentiate the effect that the treatment has on the microflora located on the surface from those in deeper layers. Highlights: The infrared treatment reduces microbial contamination in cheese rind. The efficacy of the treatment on L. monocytogenes even reaches 99.999%. The more superficially located cells are more affected by the treatment. Sponge and scraping sampling differentiate microflora according to localisation.